The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/jvi.79.20.13037-13046.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Open Reading Frame U14 Protein and Cellular p53 Interact with Each Other and Are Contained in the Virion

Abstract: A mass spectroscopic analysis of proteins from human herpesvirus 6 (HHV-6)-infected cells showed that the HHV-6 U14 protein coimmunoprecipitated with the tumor suppressor p53. The binding of U14 to p53 was verified by coimmunoprecipitation experiments in both Molt-3 cells infected with HHV-6 and 293 cells cotransfected with U14 and p53 expression vectors. Indirect immunofluorescence assays (IFAs) showed that by 18 h postinfection (hpi) U14 localized to the dot-like structures observed in both the nucleus and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 64 publications
3
36
1
Order By: Relevance
“…Intriguingly, using the Rad51 RI-1 inhibitor (27), Wallaschek et al recently reported that the Rad51 recombinase is dispensable for HHV-6A and HHV-6B integration in U2OS cells (14). Our results also suggest that abrogation of the p53 protein, which is involved in DNA repair mechanisms and interacts with the HHV-6 U14 and U19 proteins (28,29), does not affect HHV-6 chromosomal integration. Thus, our results indicate that HHV-6 U94 and the cellular p53 and Rad51 proteins are dispensable for HHV-6 integration, suggesting that other viral or cellular recombinases can complement their functions.…”
Section: Discussionsupporting
confidence: 70%
“…Intriguingly, using the Rad51 RI-1 inhibitor (27), Wallaschek et al recently reported that the Rad51 recombinase is dispensable for HHV-6A and HHV-6B integration in U2OS cells (14). Our results also suggest that abrogation of the p53 protein, which is involved in DNA repair mechanisms and interacts with the HHV-6 U14 and U19 proteins (28,29), does not affect HHV-6 chromosomal integration. Thus, our results indicate that HHV-6 U94 and the cellular p53 and Rad51 proteins are dispensable for HHV-6 integration, suggesting that other viral or cellular recombinases can complement their functions.…”
Section: Discussionsupporting
confidence: 70%
“…Human cytomegalovirus (HCMV) (Speir et al, 1994;Muralidhar et al, 1996;Tsai et al, 1996;Bonin & McDougall, 1997;Castillo et al, 2005) and possibly HHV-6A (Kashanchi et al, 1997;Takemoto et al, 2005) and HHV-6B (De Bolle et al, 2004;Takemoto et al, 2004;Øster et al, 2005) interfere with the tumour suppressor protein p53. The major functions of p53 are associated with maintaining the integrity of the genome by inducing cell-cycle arrest, senescence or apoptosis (Jin & Levine, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which HHV-6B interferes with p53 remains unclear, although two virally encoded p53-binding proteins have been identified. In HHV-6A and -6B, the U14 protein has been shown to bind p53 (Takemoto et al, 2005), and HHV-6A also encodes a p53-binding protein from the DR7 gene (Kashanchi et al, 1997). A protein product from the DR7 homologue in HHV- 6B has not yet been demonstrated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the U14-encoded tegument protein from HHV-6A and -6B may associate with p53. Interestingly, the U14 protein may tether p53 to the viral particle (Takemoto et al, 2005), although the function of this interaction has not been established. Therefore, it also remains to be investigated whether U14 may inactivate p53 during infection.…”
Section: Introductionmentioning
confidence: 99%